The Knowledge Level of Hypertension Stage 2 Patients at Harapan Keluarga Hospital Regarding Complications in the Form of Aortic Aneurysm - Sinaga, Keysha Angelica; Arsatt, Maz Isa Ansyori; Rahmat, Basuki; Wedayani, Anak Agung Ayu Niti (Jurnal Biologi Tropis, 2025)
Hypertension is a major contributor to cardiovascular complications, including aortic aneurysms, which can be fatal if left untreated. This study aims to examine the relationship between the level of hypertension, particularly stage 2, and the incidence of aortic aneurysm. A retrospective cohort analysis was conducted using medical records of 24 patients diagnosed with varying degrees of hypertension and aortic aneurysm at Harapan Keluarga Hospital in December 2024. Statistical analysis using the chi-square test revealed a significant association between hypertension severity and the incidence of aortic aneurysm (p = 0.000), with an odds ratio of 2.001 (95% CI: 2.010–2.229). These findings emphasize the need for enhanced patient education and preventive strategies, particularly among those with hypertension stage 2, to mitigate the risk of aneurysm-related complications.